2021
DOI: 10.46328/ijte.136
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality in STEM Education: Bibliometric Analysis

Abstract: Augmented reality applications in STEM education have increasing importance in recent years and it draws attention that scientific studies on this subject have gained momentum in the literature. The purpose of this research is to conduct a bibliometric analysis of studies on the use of augmented reality applications in STEM education in the literature. The Web of Science database has been used to collect the data. A total of 741 studies were accessed by going through various screening processes for the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
13
0
2
Order By: Relevance
“…The literature on STEM education shows that there are traditional reviews (Brown, 2012;Hasanah, 2020;Martín-Páez et al, 2019;Mizell & Brown, 2017;Minichiello et al, 2018) and systematic reviews (Arshad et al, 2021;Ibáñez, & Delgado-Kloos, 2018;Irwanto et al, 2022;Jin, 2021;Kayan-Fadlelmula et al, 2022Li et al, 2020) on this topic. There is also content analysis (Kaya & Ayar, 2020;London, 2018), meta-analysis (Jeong et al, 2019;Wang et al, 2022), and bibliometric analysis (Ha et al, 2020;Marín-Marín et al, 2021;Talan, 2021) studies.…”
Section: Reviews On Stem Educationmentioning
confidence: 99%
“…The literature on STEM education shows that there are traditional reviews (Brown, 2012;Hasanah, 2020;Martín-Páez et al, 2019;Mizell & Brown, 2017;Minichiello et al, 2018) and systematic reviews (Arshad et al, 2021;Ibáñez, & Delgado-Kloos, 2018;Irwanto et al, 2022;Jin, 2021;Kayan-Fadlelmula et al, 2022Li et al, 2020) on this topic. There is also content analysis (Kaya & Ayar, 2020;London, 2018), meta-analysis (Jeong et al, 2019;Wang et al, 2022), and bibliometric analysis (Ha et al, 2020;Marín-Marín et al, 2021;Talan, 2021) studies.…”
Section: Reviews On Stem Educationmentioning
confidence: 99%
“…The literature review suggests that the number of studies on STEM education has gradually increased (Chine & Larwin, 2022;Marco-Bujosa, 2021;Punzalan, 2022;Razi & Zhou, 2022;Reynders et al, 2020;Talan, 2021;Turner et al al., 2022;Wang et al, 2022). Since studies are generally suitable for the nature of the course, they are carried out in science courses or courses of a similar nature (Ceylan, 2014;Nağaç, 2018;Pekbay, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been observed that more than one sense can be actively used when using this technology, it is assumed that real learning experiences can be made with this technology. Thanks to its features, AR technology has managed to attract attention of learners in all levels of education from preschool to university (Sırakaya & Alsancak Sırakaya, 2020;Talan, 2021). In fact, research shows that AR technology is suitable for all ages (López-Belmonte et al, 2020).…”
Section: The Use Of Ar In Educationmentioning
confidence: 99%
“…In addition, AR enables students to learn by doing and increases student engagement in the classroom by making lessons more fun (Giasiranis & Sofos, 2017;Wojciechowski & Cellary, 2013;Yoon et al, 2012). Some studies have shown that AR applications have a positive impact on learning outcomes such as academic success, motivation, attention, attitude, and retention in the learning process (Akçayır & Akçayır, 2017;Batdı & Talan, 2019;Erbas & Demirer, 2019;Fidan & Tuncel, 2019;Talan, 2021). The common finding of various studies is that AR technologies can increase learning motivation, the learning process and effectiveness (Tzima, et al, 2019).…”
Section: The Use Of Ar In Educationmentioning
confidence: 99%